1998
DOI: 10.1007/bf01280710
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of signaling effect of UV-B/C light in the extended UV-A/blue-type action spectra for step-down and step-up photophobic responses in the unicellular flagellate algaEuglena gracilis

Abstract: Summary. Cultures of unicellular algal flagellate Euglena gracilisgrown in different conditions were subjected to action spectroscopy for step-down and step-up photophobic responses, respectively. The spectral region was extended into the UV-B/C as well as in the UV-A and visible regions with the Okazaki Large Spectrograph as the monochromatic light source. The photophobic responses of the cells were measured with an individual-cell assay method with the aid of a computerized video motion analyzer. In the UV-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Using the Okazaki large spectrograph and a computerized video motion analysis, Matsunaga and coworkers found that in addition to UV-A and blue light the action spectrum for photophobic responses of E. gracilis extended well into the UV-B with peaks at 270 nm (step-down response) and 280 nm (step-up response), respectively (Matsunaga et al 1998) which they attributed to the combined action of 6-biopterin and FAD. In addition, fluorescence and emission spectra of the isolated PAB proteins indicated that pterins might also be involved ).…”
Section: Earlier Results and Hypothesesmentioning
confidence: 97%
“…Using the Okazaki large spectrograph and a computerized video motion analysis, Matsunaga and coworkers found that in addition to UV-A and blue light the action spectrum for photophobic responses of E. gracilis extended well into the UV-B with peaks at 270 nm (step-down response) and 280 nm (step-up response), respectively (Matsunaga et al 1998) which they attributed to the combined action of 6-biopterin and FAD. In addition, fluorescence and emission spectra of the isolated PAB proteins indicated that pterins might also be involved ).…”
Section: Earlier Results and Hypothesesmentioning
confidence: 97%
“…The overall similarity between PAC␣ and PAC␤ is 72% at the nucleotide level. Reverse genetics (RNA interference [RNAi]; see below) revealed that PAC is not the photoreceptor of step-down photophobic responses (Iseki et al, 2002), which is consistent with the different action spectrum of this response (Matsunaga et al, 1998). The photoreceptor of phototaxis was up to now also unknown, but action spectroscopy suggested the involvement of flavins and pterins (Brodhun and Häder, 1990;Häder and Lebert, 1998).…”
mentioning
confidence: 80%
“…1A, PAC activity (1 ng ml −1 in the reaction mixture) increased proportionally to photon fluence rates in the range of 2-50 lmol m −2 s and became nearly saturated in the range of 50-100 lmol m −2 s −1 . Ranges of photon fluence rates were equivalent to those that induce physiological responses in Euglena, such as the step-up photophobic response 15 and photodispersal of several mutant strains. 16 …”
Section: Dependency On Photon Fluence Ratesmentioning
confidence: 99%